Analisis Hukum Atas Tindak Pidana Menyebarkan Ujaran Kebencian Melalui Media Sosial (Studi Kasus Putusan Nomor 283/Pid.Sus/2023/P.N.Jkt.Sel, Tanggal 10 Agustus 2023) - Angel Partungkoan Tambunan; Janpatar Simamora; Ojak Nainggolan (Lembaga Teewan Journal Solutions, 2026)
The development of social media as a digital public sphere has created new challenges in law enforcement, particularly in addressing hate speech. This study examines the application of law in Decision Number 283/Pid.Sus/2023/PN Jakarta Selatan using a normative juridical approach. The findings indicate that the panel of judges correctly applied the provisions of the Electronic Information and Transactions Law (ITE Law), especially regarding the elements of intent and hate speech based on ethnicity, religion, race, and intergroup relations (SARA). The judges also considered the principles of legal certainty, justice, and utility in reaching their decision. This study highlights the importance of firm law enforcement and preventive measures to promote a healthy and responsible digital environment.